A panoramic view on metadata application profiles of the last decade. (6th February 2014) - Malta, Mariana Curado; Baptista, Ana Alice
This paper describes a study developed with the goal to understand the panorama of the metadata Application Profiles (AP): (i) what AP have been developed so far; (ii) what type of institutions have developed these AP; (iii) what are the application domains of these AP; (iv) what are the Metadata Schemes (MS) used by these AP; (v) what application domains have been producing MS; (vi) what are the Syntax Encoding Schemes (SES) and the Vocabulary Encoding Schemes (VES) used by these AP; and finally (vii) if these AP have followed the Singapore Framework (SF). We found (i) 74 AP; (ii) the AP are mostly developed by the scientific community, (iii) the 'Learning Objects' domain is the most intensive producer; (iv) Dublin Core metadata vocabularies are the most used and are being used in all domains of application and IEEE LOM is the second most used but only inside the 'Learning Objects' application domain; (v) the most intensive producer of MS is the domain of 'Libraries and Repositories'; (vi) 13 distinct SES and 90 distinct VES were used; (vi) five of the 74 AP found follow the SF.